The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1021/ef700477a
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric Analysis Studies on the Thermal Stability of Asphaltenes: Pyrolysis Behavior of Heavy Oil Asphaltenes

Abstract: Heavy feed upgrading in the atmospheric residues (AR) desulfurizatrion process suffers from rapid catalyst deactivation by coke deposition. The main source for the coke is unconverted, refractory asphaltenes that tend to coagulate and precipitate on the catalyst surface due to incompatibility with the hydroprocessed feed. Asphaltene fractions separated from three ARs, namely Kuwait export crude (KEC), Kuwait heavy crude (KHC), and Eocene (EOC), with an API gravity of 13.5°, 8.3°, and 7.4°, respectively, were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Conversion level in thermal conversion based processes is controlled by colloidal stability of the unconverted product and the associated propensity of this to form soft coke-like substances called sediment or sludge when the colloidal stability gets below a critical limit [21][22][23][24][25][26][27]. Equipment fouling by the coke-like sediments formed in residual oil thermal conversion based processes can lead to significant economic losses because of unplanned shutdown and increased costs of operation [14,22].…”
Section: Maltene→asphaltene→sediment→cokementioning
confidence: 99%
“…Conversion level in thermal conversion based processes is controlled by colloidal stability of the unconverted product and the associated propensity of this to form soft coke-like substances called sediment or sludge when the colloidal stability gets below a critical limit [21][22][23][24][25][26][27]. Equipment fouling by the coke-like sediments formed in residual oil thermal conversion based processes can lead to significant economic losses because of unplanned shutdown and increased costs of operation [14,22].…”
Section: Maltene→asphaltene→sediment→cokementioning
confidence: 99%
“…Many reports show that first-order reaction can be acceptably applied to pyrolysis, and therefore, the pyrolysis of VR in this study is assumed to follow a first-order reaction, according to the following equation [7,[20][21][22][23][24][25].…”
Section: Kinetic Analysis Methodsmentioning
confidence: 99%
“…A number of research groups have studied asphaltene transformation in hydroprocessing [2,[4][5][6][7][8][9][10][11][12] whereas other studies have focused on the impact of thermal treatment in asphaltene conversion. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our research group has extensively concentrated on asphaltene characterization over the past few years and has fully studied the impact of thermal treatment on asphaltene molecular structure. For example, Lababidi et al [18] reported notable decrease in asphaltene molecular weight, associated with significant increase in aromaticity, as thermal cracking severity increases.…”
Section: Introductionmentioning
confidence: 99%